Asymmetric Aldol Reactions between Acetone and Benzaldehydes Catalyzed by Chiral Zn2+ Complexes of Aminoacyl 1, 4, 7, 10‐Tetraazacyclododecane: Fine‐Tuning of the Amino‐Acid Side Chains and a Revised Reaction Mechanism. Issue 9 (18th June 2013) - Itoh, Susumu; Tokunaga, Takuya; Sonoike, Shotaro; Kitamura, Masanori; Yamano, Akihito; Aoki, Shin
Abstract We previously reported that chiral Zn2+ complexes that were designed to mimic the actions of class‐I and class‐II aldolases catalyzed the enantioselective aldol reactions of acetone and its analogues thereof with benzaldehyde derivatives. Herein, we report the synthesis of new chiral Zn2+ complexes that contain Zn2+tetraazacyclododecane (Zn2+[12]aneN4) moieties and amino acids that contain aliphatic, aromatic, anionic, cationic, and dipeptide side chains. The chemical and optical yields of the aldol reaction were improved (up to 96 % ee) by using ZnL complexes of L‐decanylglycyl‐pendant [12]aneN4 (L‐ZnL7), L‐naphthylalanyl‐pendant [12]aneN4 (L‐ZnL10), L‐biphenylalanyl‐pendant [12]aneN4 (L‐ZnL11), and L‐phenylethylglycyl‐pendant [12]aneN4 ligands (L‐ZnL12). UV/Vis and circular dichroism (CD) titrations of acetylacetone (acac) with ZnL complexes confirmed that a ZnL(acac)− complex was exclusively formed and not the enaminone of ZnL and acac, as we had previously proposed. Moreover, the results of stopped‐flow experiments indicated that the complexation of (acac)− with ZnL was complete within milliseconds, whereas the formation of an enaminone required several hours. X‐ray crystal‐structure analysis of L‐ZnL10 and the ZnL complex of L‐diphenylalanyl‐pendant [12]aneN4 (L‐ZnL13) shows that the NH2 groups of the amino‐acid side chains of these ligands are coordinated to the Zn2+ center as the fourth coordination site, in addition to three nitrogen atoms of the [12]aneN4 rings. The reaction mechanism of these aldol reactions is discussed and some corrections are made to our previous mechanistic hypothesis.